Transcriptional landscape of Aspergillus niger at breaking of conidial dormancy revealed by RNA-sequencing - Novodvorska, Michaela; Hayer, Kimran; Pullan, Steven T.; Wilson, Raymond; Blythe, Martin J.; Stam, Hein; Stratford, Malcolm; Archer, David B. (BioMed Central, 2013)
Background Genome-wide analysis was performed to assess the transcriptional landscape of germinating A. niger conidia using both next generation RNA-sequencing and GeneChips. The metabolism of storage compounds during conidial germination was also examined and compared to the transcript levels from associated genes.